2002
DOI: 10.1080/0954012021000031868
|View full text |Cite
|
Sign up to set email alerts
|

Relationship power, condom use and HIV risk among women in the USA

Abstract: Women's ability to negotiate safer sexual practices, particularly condom use, is a vital component of HIV/STD prevention strategies. Gender-based power imbalances may constrain women's negotiation ability, yet few empirical studies have tested the hypothesis that sexual relationship power constitutes a key factor in condom use negotiation. In this investigation, a new measure - the Sexual Relationship Power Scale (SRPS) - was applied. Data were collected from 388, mostly Latina, women at an urban community hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
384
3
12

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(421 citation statements)
references
References 26 publications
22
384
3
12
Order By: Relevance
“…The divergent results for the relationship control subscale have also been noted in recent studies 60,61 and may indicate that it is capturing more than one construct. Prior studies have found higher total SRPS scores to be associated with fewer unprotected sexual occasions in a community sample 13 and substance abuse treatment-seeking sample. 14 The current findings support the use of multidimensional domains of power to better understand and disentangle heterosexual power dynamics in the context of sexual risk behavior.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The divergent results for the relationship control subscale have also been noted in recent studies 60,61 and may indicate that it is capturing more than one construct. Prior studies have found higher total SRPS scores to be associated with fewer unprotected sexual occasions in a community sample 13 and substance abuse treatment-seeking sample. 14 The current findings support the use of multidimensional domains of power to better understand and disentangle heterosexual power dynamics in the context of sexual risk behavior.…”
Section: Discussionmentioning
confidence: 86%
“…8,9 Gendered relationship power, herein referred to as relationship power, is a multidimensional construct with roots in individual empowerment, interpersonal dominance, and macrolevel social and structural factors, such as gender norms and economic practices favoring men. 10,11 Although research has examined the association between relationship power and sexual risk, 12,13 it has been hampered by inconsistent measurement 10 and a lack of differentiation among conceptual domains of relationship power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, findings from a growing body of research suggest that relationship factors and dynamics may be important determinants of condom use behavior, including relationship status or type; 9,26,27 relationship duration; 26,27 commitment; 28,29 power; [30][31][32][33] communication with sexual partners; 34-37 sexual decision-making; 27,30,38,39 and partner reactions to condoms. 38,40 Examining these factors in a sample of Latino men is important because of cultural characteristics that may be particularly salient to this population.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…[8][9][10] Several factors have been found to reduce consistent condom use among heterosexual men regardless of race/ethnicity, including reduced sexual pleasure and concerns about sexual performance, [11][12][13] negative outcome expectancies, 14,15 condom use selfefficacy, [16][17][18][19] attitudes towards condoms, 13,17,19 and risk perceptions. [20][21][22] Condom use also varies by partnership type, 23 relationship duration, 24,25 use of other contraceptive methods, 26,27 and sexual communication, [28][29][30][31] as well as drug and alcohol use. [32][33][34][35] Some qualitative research reports that condoms symbolize infidelity, disease status, and mistrust, which acts as a barrier to continued condom use in long-term and committed relationships.…”
Section: Introductionmentioning
confidence: 99%